“Your mother is in the struggle!” The gender dimension of the search for the disappeared in Nuevo Leon, Mexico - Nadejda Iliná (Íconos)
The United Forces for Our Disappeared in Nuevo Leon (FUNDENL) is a group of mothers and wives of people who disappeared. FUNDENL organizes autonomously to find their family members. This group is maintaining the legacy of women who have historically mobilized against disappearances, such as the Mothers of the Plaza de Mayo during the dictatorship in Argentina or the mothers of the Eureka Committee during the “dirty war” in Mexico. Why are women the ones who, in most cases, decide to search for their loved ones? The goal of this text is to analyze the gender dimension in the representations of collective identity and activism of the members of FUNDENL by observing their processes of resistance and empowerment through a feminist lens. The article argues the practices in their struggle, such as the embroidery for peace, are linked to their own experiences as women and mothers. Life histories and qualitative field work are used to understand this issue. With traditionally feminine practices, such as embroidery, the mothers and wives of FUNDENL resignify motherhood and love in the struggle for the disappeared, constructing new references about the role of women in social mobilization.